An opportunity-based explanation of entrepreneurial intention: evidence from global sourcing suppliers in China. (3rd July 2020) - Ma, Rong; Huang, Yen-Chih
Abstract: This study examines how knowledge acquisition of global sourcing suppliers in China influences their employees' entrepreneurial intention through opportunity identification. We analyzed survey data from 144 Chinese global sourcing supplier firms using structural equation modeling. The findings reveal that supplier employees were able to identify more opportunities with their employers' acquired knowledge and those identified opportunities increase employees' intention to start their own ventures. In addition to the challenge to incumbent supplier firms, our study also provides insight on potential remedies by showing that a strategic focus on the pursuit of opportunities weakens employee entrepreneurial intention. This study represents a first step toward integrating organizational and individual level variables to clarify the underlying mechanism through which firm knowledge leads to individual entrepreneurial intention. ABSTRAIT: Cette étude examine comment l'acquisition des connaissances chez les fournisseurs à l'échelle mondiale de services d'externalisation basés en Chine influence les intentions entrepreneuriales des employés de ces fournisseurs, à travers l'identification d'opportunités. En utilisant la modélisation par équations structurelles, nous avons analysé les données d'une enquête conduite parmi 144 entreprises chinoises proposant des services d'externalisation à l'échelle mondiale. Les résultats révèlent que les employés de ces entreprises étaient capables, grâce aux connaissances acquises par leurs employeurs, d'identifier un nombre plus important d'opportunités; et que cette détermination des opportunités renforçait leur intention de démarrer leurs propres entreprises. Au-delà de ce défi pour les entreprises en place, notre étude révèle des solutions potentielles en montrant qu'une orientation stratégique pour la poursuite des opportunités affaiblit les intentions entrepreneuriales des employés. Cette étude représente une première étape vers l'intégration de variables organisationnelles et individuelles visant à clarifier le mécanisme sous-jacent à travers lequel les connaissances dans les entreprises conduisent à l'intention entrepreneuriale individuelle.